2002
DOI: 10.1159/000065506
|View full text |Cite
|
Sign up to set email alerts
|

Aging Liver

Abstract: Aging is characterized by a progressive decline of cellular functions. The aging liver appears to preserve its function relatively well. Aging is associated in human liver with morphological changes such as decrease in size attributable to decreased hepatic blood flow. Ultrastructural analysis of the human liver has revealed that the integrity of mitochondria and enzymatic activity remain mostly unchanged with aging. Reactive oxygen species (ROS) are involved in the aging process and result mainly from nonenzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(51 citation statements)
references
References 84 publications
2
48
1
Order By: Relevance
“…We detected lipofuscin in 41 of 68 cadaveric livers (60.2%). Although the data are in accordance with the notion that lipofuscin expression is associated with the liver of old age (Anantharaju et al, 2002;Schmucker, 2005), its absence (in the reaming 40% of the aged cadaveric livers) suggests that lipofuscin is not sine qua non of the aging liver. Given the cadaver age range 56-100, the question was raised which liver pathologic lesions were likely in the very elderly.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…We detected lipofuscin in 41 of 68 cadaveric livers (60.2%). Although the data are in accordance with the notion that lipofuscin expression is associated with the liver of old age (Anantharaju et al, 2002;Schmucker, 2005), its absence (in the reaming 40% of the aged cadaveric livers) suggests that lipofuscin is not sine qua non of the aging liver. Given the cadaver age range 56-100, the question was raised which liver pathologic lesions were likely in the very elderly.…”
Section: Resultssupporting
confidence: 86%
“…The question was raised whether elderly cadavers express lipofuscin, an aging pigment associated with the liver of older people (Tygstrup et al, 1965;Anantharaju et al, 2002;Schmucker, 2005). Accordingly, we looked for lipofuscin in H&E section, which appears as yellowbrown granules in the hepatocytes.…”
Section: Lipofuscin Detectionmentioning
confidence: 99%
“…As an oxidative stress-inducible gene, basal increases in gadd153 expression are consistent with the idea that aging is associated with elevated levels of ROS and chronic oxidative stress (4,50). However, it is also possible that changes in gadd153 contribute to elevations in ROS, as we have shown that ectopic expression of Gadd153 in rat fibroblasts leads to increased levels of ROS (41).…”
Section: Ros Contribute To Increasing Gadd153 Levels By Egf Treatmentsupporting
confidence: 83%
“…This is probably due to a reduction in liver mass and blood flow [52]. As a result, the bioavailability of drugs undergoing extensive first-pass metabolism such as propranolol and labetalol can be significantly increased [53][54][55].…”
Section: First-pass Metabolism and Bioavailabilitymentioning
confidence: 99%